Eksperimen Pengaruh Variasi Diameter Nozzle Injektor dan Tekanan Injeksi Terhadap Efisiensi Konsumsi Bahan Bakar Mesin Diesel - Aditya Kris Samudera; Alfat Sulistiya Nugraha; Ninik Martini (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
Diesel engines are widely used in the transportation and industrial sectors due to their high thermal efficiency and good operational durability. However, increased fuel consumption due to inefficiency of the injection system remains a common problem. Injector characteristics, particularly nozzle diameter and injection pressure, are important factors that affect the quality of fuel atomization, air-fuel mixing, and combustion efficiency. An inappropriate combination of parameters can cause suboptimal combustion and increase fuel consumption. This study aims to analyze the effect of variations in nozzle diameter and injection pressure on fuel consumption efficiency in diesel engines. The method used is an experiment with variations in nozzle diameter of 0.150 mm, 0.152 mm, and 0.154 mm and injection pressures of 400 bar, 420 bar, and 440 bar. Tests were conducted at engine speeds of 500 rpm, 1000 rpm, and 1500 rpm with a fuel consumption measurement time of one minute for each parameter combination. Fuel consumption was measured using the volumetric method and analyzed through the fuel volumetric flow rate, fuel mass flow rate, Brake Power (BP), and Brake Specific Fuel Consumption (BSFC). The results showed that the combination of a nozzle diameter of 0.150 mm and an injection pressure of 400 bar produced the lowest BSFC value, thus providing the best fuel consumption efficiency. Meanwhile, the combination of a nozzle diameter of 0.152 mm and an injection pressure of 420 bar showed the closest condition to optimal because it was able to provide a balance between atomization quality and the amount of fuel injected, resulting in efficient and stable combustion. Thus, the efficiency of a diesel engine is influenced by the balance of nozzle size and injection pressure, not solely by the lowest fuel consumption.